Extensive nrDNA ITS polymorphism in Lycium: Non-concerted evolution and the identification of pseudogenes - Zhang, Jiao; Chi, Xiulian; Zhong, Juying; Fernie, Alisdair; Alseekh, Saleh; Huang, Luqi; Qian, Dan (Frontiers in Plant Science, 2022)
The internal transcribed spacer (ITS) is one of the most extensively sequenced molecular markers in plant systematics due to its generally concerted evolution. While non-concerted evolution has been found in some plant taxa, such information is missing in Lycium. Molecular studies of six species and two variants of the genus Lycium revealed high levels of intra- and inter-individual polymorphism in the ITS, indicating non-concerted evolution. All genomic DNA ITS paralogues were identified as putative pseudogenes or functional paralogues through a series of comparisons of sequence features, including length and substitution variation, GC content, secondary structure stability, the presence of conserved motifs in the 5.8S gene, and the rate of evolution. Approximately 60% of ITS pseudogenes could be easily detected. Based on phylogenetic analysis, all pseudogenes were highly distinct from their corresponding functional copies, tended to evolve neutrally, and clustered randomly together in the evolutionary tree. The results probably suggest that this ITS non-concerted evolution is related to recent divergence between tandem repeats within the Lycium genome and hybridization between species. Our study complements those of pseudogenes in plant taxa and provides a theoretical basis for the phylogeny and genetic origin of the genus Lycium while having important implications for the use of ITS molecular markers for phylogenetic reconstruction.